Business coaching processes that facilitate the successful implementation of business improvement projects - Sunet Klopper; Salomé Van Coller-Peter (International Journal of Evidence Based Coaching and Mentoring, 2018)
This article is a summary of a research assignment investigating the Business Coaching Processes (BCPs) that support the implementation of Business Improvement Projects (BIPs) in order to gain a better understanding of the coaching processes and tools applied. The selection of coaching processes and tools is most often influenced by the coaching context, the background of the coach and the outcomes required. This study found that the selection and application of processes and tools were influenced by factors not considered and showed a 45% deviation from current literature. This study reflects actual practices applied to support the implementation of BIPs.